2009
DOI: 10.1039/b809437n
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic acids: a group of medicinally important compounds

Abstract: This review, containing over 276 references, covers the progress made in the chemistry and bioactivity of this important group of triterpenoids. Though initially known for their anti-inflammatory and anti-arthritic activities through a unique 5-LO inhibition mechanism, boswellic acids have recently attained significance due to their anti-cancer properties. The phytochemistry and chemical modifications, including mechanism of action, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 207 publications
4
119
0
1
Order By: Relevance
“…The diverse array of terpenoid structures and functions has provoked increased interest in their commercial use. Terpenoids have been found to be useful in the prevention and therapy of several diseases, including cancer, and also to have antimicrobial, antifungal, antiparasitic, antiviral, anti-allergenic, antispasmodic, antihyperglycemic, antiinflammatory, and immunomodulatory properties [45][46][47][48] . In addition, terpenoids can be used as protective substances in storing agriculture products as they are known to have insecticidal properties [49] .…”
Section: Terpenoidsmentioning
confidence: 99%
“…The diverse array of terpenoid structures and functions has provoked increased interest in their commercial use. Terpenoids have been found to be useful in the prevention and therapy of several diseases, including cancer, and also to have antimicrobial, antifungal, antiparasitic, antiviral, anti-allergenic, antispasmodic, antihyperglycemic, antiinflammatory, and immunomodulatory properties [45][46][47][48] . In addition, terpenoids can be used as protective substances in storing agriculture products as they are known to have insecticidal properties [49] .…”
Section: Terpenoidsmentioning
confidence: 99%
“…by modulating DNA methylation in colorectal cancer cells Hon-Chiu E. Leung, 3 C. Richard Boland 1 and Ajay Goel DNA hypermethylation of CpG islands located within the promoter regions of tumor suppressor genes is a common epigenetic alteration involved in most human cancers. Unlike genomic epigenetic alterations, including aberrant methylation genes is potentially reversible with therapeutic agents.…”
Section: Boswellic Acid Induces Epigenetic Alterationsmentioning
confidence: 99%
“…[1][2][3][4][5] Acetyl-11-keto-β-boswellic acid (AKBA), one of the major active boswellic acids present in boswellia extracts, is a pentacyclic terpenoid, which has been shown to have antitumor effects in different types of tumor cells including colon, 6,7 prostate, 8,9 leukocytes, 10 liver 11 and brain. 12 Several earlier studies have reported inhibitory effects of AKBA on the nuclear factor kappa B (NFκB), 13 and the signal transducer and activator of transcription-3 (STAT-3)-related pathways, 14 which potentiate apoptosis and inhibit angiogenesis in neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 4 and KBA was isolated in a way analogous to an earlier reported method. 1 Single crystals of the compound were grown by a slow evaporation technique using ethyl acetate as the solvent system. Because of the absence of any significant anomalous scatterers in the compound, the absolute configuration of the molecule has not been determined by an X-ray diffraction experiment, and the assumed chirality of the molecule was determined from the parent molecule.…”
mentioning
confidence: 99%
“…Because of the absence of any significant anomalous scatterers in the compound, the absolute configuration of the molecule has not been determined by an X-ray diffraction experiment, and the assumed chirality of the molecule was determined from the parent molecule. 1 The crystallographic data are summarized in Table 1. Selected bond lengths, bond angles and endocyclic torsion angles are given in Table 2S.…”
mentioning
confidence: 99%